2020
DOI: 10.1084/jem.20190634
|View full text |Cite|
|
Sign up to set email alerts
|

ACKR4 restrains antitumor immunity by regulating CCL21

Abstract: Current immunotherapies involving CD8+ T cell responses show remarkable promise, but their efficacy in many solid tumors is limited, in part due to the low frequency of tumor-specific T cells in the tumor microenvironment (TME). Here, we identified a role for host atypical chemokine receptor 4 (ACKR4) in controlling intratumor T cell accumulation and activation. In the absence of ACKR4, an increase in intratumor CD8+ T cells inhibited tumor growth, and nonhematopoietic ACKR4 expression was critical. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 57 publications
0
25
2
Order By: Relevance
“…Recently, it was shown that the atypical chemokine receptor ACKR4 restrains antitumor immunity by decreasing intratumor CCL21. Deletion of ACKR4 in mice resulted in increased intratumor CCL21, retention of CD103+ dendritic cells, and an increase in CD8+ T-lymphocytes, which inhibited tumor growth (12).…”
Section: Chemokine Cues For Lymph Node Homing/disseminationmentioning
confidence: 99%
“…Recently, it was shown that the atypical chemokine receptor ACKR4 restrains antitumor immunity by decreasing intratumor CCL21. Deletion of ACKR4 in mice resulted in increased intratumor CCL21, retention of CD103+ dendritic cells, and an increase in CD8+ T-lymphocytes, which inhibited tumor growth (12).…”
Section: Chemokine Cues For Lymph Node Homing/disseminationmentioning
confidence: 99%
“…6,10 ACKR4 is best known for its role in shaping the gradient of CCL19 and CCL21 for CCR7-expressing DCs in the subcapsular sinuses of lymph nodes during the initiation phase of the adaptive immune response. 11,12 ACKR4 is also involved in antitumor immunity and modulates epithelial-mesenchymal transition and metastasis, [13][14][15] and studies with ACKR4-deficient mice in an EAE model also demonstrated the receptor implication in autoimmune diseases notably by F I G U R E 1 Systematic reassessment of human ACKR4 activation by chemokines using a highly sensitive -arrestin recruitment assay based on NanoBiT technology. (A) -arrestin-1 and -arrestin-2 recruitment to ACKR4 in response to all known human and 2 viral chemokines (100 nM).…”
Section: Brief Conclusive Reportmentioning
confidence: 99%
“…ACKR4 is best known for its role in shaping the gradient of CCL19 and CCL21 for CCR7‐expressing DCs in the subcapsular sinuses of lymph nodes during the initiation phase of the adaptive immune response 11,12 . ACKR4 is also involved in antitumor immunity and modulates epithelial‐mesenchymal transition and metastasis, 13–15 and studies with ACKR4‐deficient mice in an EAE model also demonstrated the receptor implication in autoimmune diseases notably by accelerated disease onset an more severe symptomes attributable to increased Th17 response 4,16 . Of note, 2 ACKR4‐defincient mouse strains (ACKR4 −/− and ACKR4 GFP/GFP ) are available and display distinct phenotypes.…”
Section: Brief Conclusive Reportmentioning
confidence: 99%
“…KIAA1549 belongs to the UPF0606 family and is related to oncogenic MAPK signaling [24]. Atypical chemokine receptor 4 (ACKR4), which is a receptor for C-C type chemokines, has been shown to bind T cells and dendritic cell-activated chemokines and plays a signi cant role in controlling the migration of immune and cancer cells [25]. These ndings indicated that a number of mRNAs have changed during the peri-operative period that may play a role in the development of CRC.…”
Section: Discussionmentioning
confidence: 99%